Normas de publicación y guía para autores. Actualización 2021 - Naranjo-Dominguez, Adrian; Valdés Martín, Alexander; Crespo, Iria; Larrinaga Sandrino, Vanessa; Rivas Estany, Eduardo (Revista Cubana de Cardiología y Cirugía Cardiovascular, 2021)
Normas de publicación y guía para autores. Actualización 2021